Combination of Static Magnetic Fields and Peripheral Nerve Stimulation Can Alter Focal Cortical Excitability - Nojima, Ippei; Koganemaru, Satoko; Mima, Tatsuya (Frontiers in Human Neuroscience, 2016)
For clinical application of transcranial static magnetic stimulation (tSMS), it is important to achieve a focal target cortical stimulation. Previous study suggested that the associative stimulation combining non-invasive stimulation of the motor cortex (M1) and the peripheral nerve stimulation (PNS) may be useful to produce cortical excitability change. To test this hypothesis, we measured the M1 excitability and intracortical circuits by using transcranial magnetic stimulation (TMS) before and after the tSMS of short duration (5 min) combined with PNS. Thirty-three normal volunteers were participated; tSMS+PNS (n=11), sham+PNS (n=11) and tSMS alone (n=11). We found the transient suppression of the motor-evoked potential (MEP) of the right abductor pollicis brevis (APB) muscle, but not of the abductor digiti minimi (ADM) muscle, when combining tSMS with PNS over median nerve at the wrist. The lack of suppressive effect on APB in tSMS alone with short duration is in accord with the previous observation. In addition, the tendency of transient enhancement of the short-latency intracortical inhibition was observed immediately after intervention in the tSMS+PNS group. These findings show that the combination of tSMS and PNS can induce the cortical excitability change in target cortical motor area and potentiate the suppression effect.